From biomarkers to a clue of biology: a computation-aided perspective of immune gene expression profiles in human type 1 diabetes - Han, Dongmei; Cai, Xiaodong; Wen, Ji; Kenyon, Norma; Chen, Zhibin (Frontiers in Immunology, 2012)
Dysregulated expression of key immune genes may cause breakdown of immunological tolerance and development of autoimmune disorders such as type 1 diabetes (T1D). General immune insufficiencies have also been implicated as a trigger of autoimmunity, due to their potential impact on immune homeostasis. Recent studies have detected evidence of systemic reduction in immune gene expression in long-term diabetic patients but the changes were not present before or at T1D onset. The changes could not be merely correlated with alteration in metabolic parameters. The studies also identified a dynamic expression pattern of several well-known as well as little-studied, immune-related genes during the course of T1D. An intriguing “ratio profile” of immune regulatory genes, such as CTLA-4 and members of the S100 family, versus “baseline” immune genes, such as CD3G, prompted us to further examine immune gene expression relationships for a set of molecules representing T cells, B cells and myeloid cells. No evidence was found to suggest an overall breach of tolerance equilibrium in T1D. Perplexingly, patients with long-term T1D presented a gene expression profile that was surprisingly more coordinated in analyses of “networking” relationship. Computational analyses of the “ratio profiles” or “relationship profiles” of immune gene expression might provide a clue for further studies of immunobiology in human T1D and other autoimmune diseases, as to how the profiles may be related to the pathogenic cause of the disease, to the effect of the diseases on immune homeostasis, or to an immunological process associated with the course of the diseases but is neither a direct cause nor a direct effect of the diseases.